High Epoxidation Yields of Vegetable Oil Hydrolyzates and Methyl Esters by Selected Fungal Peroxygenases - González-Benjumea, Alejandro; Marques, Gisela; Herold-Majumdar, Owik M.; Kiebist, Jan; Scheibner, Katrin; del Río, José C.; Martínez, Angel T.; Gutiérrez, Ana (Frontiers in Bioengineering and Biotechnology, 2021)
Epoxides of vegetable oils and free and methylated fatty acids are of interest for several industrial applications. In the present work, refined rapeseed, sunflower, soybean and linseed oils, with very different profiles of mono- and polyunsaturated fatty acids, were saponified and transesterified, and the products treated with wild unspecific peroxygenases (UPOs, EC 1.11.2.1) from the ascomycete Chaetomium globosum (CglUPO) and the basidiomycete Marasmius rotula (MroUPO), as well as with recombinant UPO of the ascomycete Humicola insolens (rHinUPO), as an alternative to chemical epoxidation that is nonselective and requires strongly acidic conditions. The three enzymes were able of converting the free fatty acids and the methyl esters from the oils into epoxide derivatives, although significant differences in the oxygenation selectivities were observed between them. While CglUPO selectively produced “pure” epoxides (mono and/or diepoxides), MroUPO formed also hydroxylated derivatives of these epoxides, especially in the case of the oil hydrolyzates. Hydroxylated derivatives of non-epoxidized unsaturated fatty acids were practically absent in all cases, due to the preference of the three UPOs selected for this study to form the epoxides. Moreover, rHinUPO, in addition to forming mono and diepoxides of oleic and linoleic acid (and their methyl esters), respectively, like the other two UPOs, was capable of yielding the triepoxides of α-linolenic acid and its methyl ester. These enzymes appear as promising biocatalysts for the environmentally-friendly production of reactive fatty-acid epoxides given their self-sufficient monooxygenase activity with selectivity towards epoxidation, and the ability to epoxidize, not only isolated pure fatty acids, but also complex mixtures from oil hydrolysis or transesterification containing different combinations of unsaturated (and saturated) fatty acids.